Multimorphism and gap opening of charge-density-wave phases in monolayer VTe2 - Liu, Meizhuang; Wu, Changwei; Liu, Zizhao; Wang, Zhiqiang; Yao, Dao-Xin; Zhong, Dingyong (Nano research, 2020)
Vanadium dichalcogenides have attracted increasing interests for the charge density wave phenomena and possible ferromagnetism. Here, we report on the multiphase behavior and gap opening in monolayer VTe 2 grown by molecular beam epitaxy. Scanning tunneling microscopy (STM) and spectroscopy study revealed the (4×4) metallic and gapped (2√3×2√3) charge-density wave (CDW) phases with an energy gap of ≈ 40 meV. Through the in-plane condensation of vanadium atoms, the typical star-of-David clusters and truncated triangle-shaped clusters are formed in the (4×4) and (2√3×2√3) phases respectively, resulting in different surface morphologies and electronic structures as confirmed by density functional theory (DFT) calculations with on-site Coulomb repulsion. The CDW-driven reorganization of the atomic structure weakens the ferromagnetic superexchange coupling and strengthens the antiferromagnetic exchange coupling on the contrary, suppressing the long-range magnetic order in monolayer VTe 2 . The electron correlation is found to be important to explain the gap opening in the (2√3×2√3) phase.